Leoligin, the major lignan from Edelweiss, inhibits 3-hydroxy-3-methyl-glutaryl-CoA reductase and reduces cholesterol levels in ApoE −/− mice. (October 2016) - Scharinger, Bernhard; Messner, Barbara; Türkcan, Adrian; Schuster, Daniela; Vuorinen, Anna; Pitterl, Florian; Heinz, Katharina; Arnhard, Kathrin; Laufer, Günther; Grimm, Michael; Stuppner, Hermann; Oberacher, Herbert; et al.
Abstract: The health benefit through the control of lipid levels in hyperlipidaemic individuals is evident from a large number of studies. The pharmacological options to achieve this goal shall be as specific and personalized as the reasons for and co-factors of hyperlipidaemia. It was the goal of this study to reveal the impact of leoligin on cholesterol levels and to define its mechanism of action. Oral application of leoligin in ApoE −/− mice led to significantly reduced total serum cholesterol levels and a reduction in postprandial blood glucose peak levels. In the absence of biochemical signs of toxicity, leoligin treatment resulted in reduced weight gain in mice. The effects of leoligin on serum cholesterol levels may be due to a direct inhibition of 3-hydroxy-3-methyl-glutaryl-CoA reductase (HMGCR) by a unique, non-statin-like binding mode. Postprandial serum glucose peaks may be reduced by a mild peroxisome proliferator-activated receptor-gamma (PPAR-γ) agonistic activity of leoligin. No effect on atherosclerotic plaque size was observed. As a non-toxic, cholesterol-, peak glucose-, and weight gain-lowering compound, leoligin continues to fulfil characteristics of a potential agent for the treatment of cardiovascular disease (CVD). The counterregulatory overexpression of hepatic HMGCR in leoligin treated animals possibly explains the missing permanent anti-atherosclerotic effect. Highlights: Leoligin reduces LDL cholesterol levels and improves LDL/HDL and LDL/total cholesterol ratios. Leoligin's beneficial effects on cholesterol levels can be explained by its HMG-CoA reductase inhibitory activity. In silico modelling suggest an unconventional interaction of Leoligin with HMG-CoA-reductase. Leoligin reduces peak glucose levels in glucose tolerance test and reduces weight gain.